The Influence of Relationship Marketing and Word-Of-Mouth On Service Selection Decisions with Trust as A Mediating Variable - Fadhila Azzahra; Tibrani Tibrani; Rizki Eka Putra (Jurnal Ilmiah Accusi, 2026)
Patient behavior in selecting clinical laboratory services is heavily influenced by the quality of interactions and recommendations they receive. However, a research gap exists regarding the psychological mechanisms driving these choices in "credence good" settings like clinical laboratories, where technical quality cannot be easily evaluated by patients. Addressing this gap, this study offers novelty by comparatively examining how Relationship Marketing (RM) and Word-of-Mouth (WOM) shape service selection decisions at Osmaro Clinical Laboratory in Batam, specifically through the mediating lens of trust. Using a causal-quantitative approach, data from 160 purposively sampled respondents were analyzed via SEM-PLS (SmartPLS 4). Findings confirm that both RM and WOM positively influence decisions, with the model demonstrating strong explanatory power (Trust R² = 0.628; Service Selection R² = 0.715). Notably, WOM emerges as a stronger driver of trust than RM. Theoretically, this extends healthcare marketing literature by proving that in opaque medical services, peer validation outweighs institutional relational efforts in establishing foundational trust. Managerially, laboratory operators must shift from relying solely on internal service protocols; resource allocation should prioritize safeguarding data ethics and curating exceptional patient experiences that organically stimulate positive WOM, as trust remains the ultimate catalyst for securing patient loyalty